A. MUKTI ALI'S THINKING IN INDONESIAN ISLAMIC EDUCATION POLICY - Zuhri, Faisal (Journal Of Islamic Education And Pesantren, 2021)
The purpose of this study is to describe the implications of Mukti Ali's thinking in Islamic education policies in Indonesia. This study uses a qualitative method of literature. This study concludes that Mukti Ali's policy thinking includes: a) Improving Islamic educational institutions, b) Modernizing Islamic boarding schools, c) Reforming Islamic higher education institutions or state Islamic religious institutes, d) IAINing the quality of education. Mukti Ali used an integral and interdepamental approach in determining Islamic education policies while serving as Minister of Religion. The 3 ministerial decree issued during the time of the minister of religion Mukti Ali was developed in 1986 through the MAN-PK pilot project, so that Islamic education, especially madrasas, began to appear. In the following year, UUSPN No. 2 of 1989 until UUSPN No. 20 of 2003 became the basis for policies that emphasized that religious education had the right to be received by every student at the elementary, secondary and tertiary levels. Keywords: thoughts, educational policies, Islamic educational institutions. PEMIKIRAN A. MUKTI ALI DALAM KEBIJAKAN PENDIDIKAN ISLAM INDONESIA Abstrak Tujuan penelitian ini adalah mendeskribsikan implikasi pemikiran Mukti Ali dalam kebijakan pendidikan Islam di Indonesia. Penelitian ini menggunakan metode kualitatif kepustakaan. Penelitian ini menympulkan bahwa pemikiran kebijakan Mukti Ali meliputi: a) Pembenahan lembaga pendidikan islam, b) Modernisasi lembaga pesantren, c) Pembenahan lembaga pendidikan tinggi Islam atau institut agama Islam negeri, d) Peningkatan mutu pendidikan IAIN. Mukti Ali menggunakan pendekatan integral dan interdepamental dalam menentukan kebijakan pendidikan islam selama menjabat Menteri Agama. SKB 3 menteri yang diterbitkan pada masa menteri agama Mukti Ali dikembangkan pada tahun 1986 melalui pilot projet MAN-PK, sehingga pendidikan Islam khususnya madrasah mulai nampak perkembangannya. Pada tahun selanjutnya dikeluarkan UUSPN No. 2 Tahun 1989 sampai pada UUSPN No.20 Tahun 2003 menjadi landasan kebijakan yang menekankan bahwa pendidikan agama berhak diterima oleh setiap peserta didik baik ditingkat dasar, menengah dan perguruan tinggi. kata kunci: pemikiran, kebijakan pendidikan, lembaga pendidikan Islam